(untitled) (Research, Society and Development, 2023)
Introduction: lithium is the most efficient long-term therapy in the treatment and prevention of bipolar disorders as a mood stabilizer, and when in use, it is necessary to have constant monitoring of the plasma concentration to avoid cases of intoxication, as it is a substance of low therapeutic index. Objective: to identify the potential risks of organic and systematic adverse reactions to lithium carbonate, as well as drug interactions that can contribute to serious complications for the patient. Methodology: this is a descriptive research of the Integrative Literature Review type. Studies published in the period between 2015 and 2021 were considered, and relevant sources inherent to the theme were analyzed, using as one of the main criteria the choice of current, original and international articles. Results: even when used in therapeutic doses, lithium can cause important changes, such as a decrease in GFR, which in a feedback way lead to acute lithium intoxication, causing cardiac, renal and mental state alterations. Factors such as age and time of drug use must be considered in a directly proportional way to assess the extent of injuries and changes suffered by the patient. Conclusion: despite all adverse effects resulting from the use of lithium, this treatment remains the gold standard in the treatment of bipolar disorder. Therefore, it is important to monitor patients’ blood glucose and the functions of multiple systems in order to regulate doses or even associate lithium with other medications in order to reduce adverse effects, if necessary.